INFLUENCE OF FAMILY SUPPORT AND EDUCATION ON STUDENTS' ENTREPRENEURIAL INTENTIONS VIA INSPIRATION - Fauzan, Muhammad Gilang; Zahra, Siti Fatimah; Suparno (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study analyzes the influence of family support and entrepreneurship education on the entrepreneurial intention of Faculty of Economics and Business, Universitas Negeri Jakarta 2022 batch students, with entrepreneurial inspiration as a mediator. Using a quantitative survey, data was collected from 132 students online and analyzed with SEM-PLS. Results show that family support and entrepreneurship education positively influence entrepreneurial intention and inspiration. Entrepreneurial inspiration also positively influences entrepreneurial intention. Nevertheless, the mediation effect of inspiration is relatively low. This model has good explanatory and predictive power, emphasizing the importance of family support, education, and inspiration in shaping students' entrepreneurial intention.